2022
DOI: 10.1002/ente.202200899
|View full text |Cite
|
Sign up to set email alerts
|

Li4Ti5O12‐Based Battery Energy Storage System with Dual‐Phase Cathode

Abstract: Lithium‐ion batteries with spinel Li4Ti5O12 materials as anode, which can offer fast charge times, high power output, superior safety, and long life, are considered to be a competitive choice for grid‐scale energy storage systems (ESS). Herein, a 10 Ah lithium–titanate battery with lithium cobalt oxide–lithium nickel cobalt manganese oxide dual‐phase cathode is developed and its application in 100 kWh‐level ESS is investigated. The 10 Ah single battery demonstrates a specific capacity of 79 Wh kg−1 with a high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
(33 reference statements)
0
1
0
Order By: Relevance
“…The 125 kWh ESS shows an energy efficiency of 97.82% and 89.97% at 0.2 and 1.5 C System , respectively. Self-discharge and constant power tests confirmed that this battery is suitable for storing intermittent power from renewable sources such as solar and wind, and its ability to smooth the fluctuating power is confirmed by coordinating with a wind power system [ 22 ]. The use of NCM as the cathode is the first solution to increase the energy density of the LTO-based lithium-ion batteries since NCM belongs to the family of high-voltage cathode elements, compensating for the operating voltage of 1.55 V of LTO.…”
Section: Introductionmentioning
confidence: 99%
“…The 125 kWh ESS shows an energy efficiency of 97.82% and 89.97% at 0.2 and 1.5 C System , respectively. Self-discharge and constant power tests confirmed that this battery is suitable for storing intermittent power from renewable sources such as solar and wind, and its ability to smooth the fluctuating power is confirmed by coordinating with a wind power system [ 22 ]. The use of NCM as the cathode is the first solution to increase the energy density of the LTO-based lithium-ion batteries since NCM belongs to the family of high-voltage cathode elements, compensating for the operating voltage of 1.55 V of LTO.…”
Section: Introductionmentioning
confidence: 99%